2016
DOI: 10.1186/s13014-016-0692-9
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemoradiotherapy instead of revision radical resection after local excision for high-risk early rectal cancer

Abstract: BackgroundAfter local excision of early rectal cancer, revision radical resection is recommended for patients with high-risk pathologic stage T1 (pT1) or pT2 cancer, but the revision procedure has high morbidity rates. We evaluated the efficacy of adjuvant concurrent chemoradiotherapy (CCRT) for reducing recurrence after local excision in these patients.MethodsEighty-three patients with high-risk pT1 or pT2 rectal cancer underwent postoperative adjuvant CCRT after local excision. We defined high-risk features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
3
22
1
Order By: Relevance
“…In the Spanish study [18] 13 of 28 patients developed complications of radiotherapy (8 grade I, 5 grade II) and all were managed conservatively. The Korean study [21] noted early proctitis (grade 2) in 11% of patients. The same number showed asymptomatic proctitis later at follow-up.…”
Section: Adjuvant Radiotherapymentioning
confidence: 97%
See 1 more Smart Citation
“…In the Spanish study [18] 13 of 28 patients developed complications of radiotherapy (8 grade I, 5 grade II) and all were managed conservatively. The Korean study [21] noted early proctitis (grade 2) in 11% of patients. The same number showed asymptomatic proctitis later at follow-up.…”
Section: Adjuvant Radiotherapymentioning
confidence: 97%
“…Two more recent Asian studies used adjuvant CRT in a more structured regime for tumors with adverse histopathological features. A Korean study [21] looked at 83 patients after local excision; 70% had transanal excision and 30% underwent EMR or EMD. The standard adjuvant treatment was radiotherapy (50.4 Gy over 5 weeks) with concurrent chemotherapy.…”
Section: Adjuvant Radiotherapymentioning
confidence: 99%
“…A couple of more recent studies have used radiotherapy in a more formalized regime. A Korean study of 83 patients having chemoradiotherapy after local excision for high‐risk T1 and any T2 tumours recorded three instances of local recurrence (3.7%) at a median follow‐up of 5.1 years. Sasaki et al .…”
Section: Discussionmentioning
confidence: 99%
“…A couple of more recent studies have used radiotherapy in a more formalized regime. A Korean study [8] of 83 patients having chemoradiotherapy after local excision for high-risk T1 and any T2 tumours recorded three instances of local recurrence (3.7%) at a median follow-up of 5.1 years. Sasaki et al [9] reported a multicentre Japanese clinical trial in which 57 patients with low rectal cancer received chemoradiotherapy after local excision.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding postoperative chemo/radiotherapy, NCCN supported this indication for T1–2 tumours after transanal excision, mainly as an alternative to radical surgery. In the same way, only NCCN guidelines advised adjuvant treatment for stage II cancer.…”
Section: Discussionmentioning
confidence: 99%